Tratamento do lixiviado do aterro sanitário de Maringá-PR por processos de ozonização e ozonização catalítica - Scandelai, Ana Paula Jambers (2015)
The landfill leachate is the liquid generated by the decomposition of solid waste in a landfill. This effluent presents dark coloration and several pollutants in its composition, as high contents of turbidity, organic and inorganic compounds, ammonia nitrogen, toxicity and refractory compounds to biodegradation, how humic substances. These characteristics indicate the necessity to perform a treatment aiming the improvement of its quality before to be pounced on a river. The advanced oxidation processes (AOP) have been an alternative to treatment of landfill leachate, due to its potentiality of mineralization of pollutants or transformation into more easily biodegradable compounds. Thus, the present work objectives to evaluate the efficiency of ozonation (O3), catalytic ozonation with TiO2 (O3/TiO2) and catalytic ozonation with ZnO (O3/ZnO) AOP, under different conditions of initial pH and concentration of catalyst in suspension, to the treatment of landfill leachate generated in the landfill of Maringá-PR. First of all, the landfill leachate was subjected to 30 minutes of treatment by processes: O3 (in 4, raw (7,5-7,7) and 11 pH), O3/TiO2 (in 4, raw and 11,0 pH) and O3/ZnO (in 1 4,3 and raw pH), with catalyst concentrations of de 0,5 e 1,0 g L-1. The best efficiencies were presented by the processes O3 in 4 pH, O3/TiO2 in 4 pH, independently of catalyst concentrations, and O3/ZnO in raw pH and concentration of 0,5 g ZnO L-1. The catalytic process with ZnO showed more efficient than the other tested processes. Posteriorly, a new landfill leachate was subjected to processes of O3, O3/TiO2 and O3/ZnO, with different values initial pH (3, 5 and raw: 7,0-7,5), fixed catalyst concentration (0,5 g L-1) and time of reaction of 120 minutes. In general, the major removal were obtained by processes at pH 3 or raw, until 90 minutes of treatment, and the catalytic process with ZnO showed to be more effective than the catalytic process with TiO2, independently of the initial pH of the leachate. From these results, a new landfill leachate was subjected to treatment with O3, O3/TiO2 and O3/ZnO, in initial raw pH (6,9) and catalyst concentration of 0,5 g L-1 and 90 minutes of reaction. The processes effiency in the treatability of landfill leachate was investigated through the removal of the following parameters: organic material (COD, BOD5, DOC), color, turbidity, metals, nitrogen compounds, phosphorus, solid series, humic substances and organic compounds, identified by GC-MS and 1H NMR. It was verified that the most evaluated parameters were efficiently removed by ozonation in raw pH and that the catalytic processes with TiO2 and with ZnO, in raw pH, didn´t elevated significantly these removals. Through the analysis of GC-MS and 1H NMR, it was observed that three oxidation processes indicated qualitative reduction of organic and aromatic compounds the raw leachate, and by-products formed during the processes had low molar mass.